(untitled) (Bulletin of criminological association of Ukraine, 2023)
It is noted that a forest is a natural (or artificially created) ecosystem, the main components of which are woody vegetation, shrubs, grass cover, soils, plant etc. It is formed as a result of long-term natural development or human economic activity. The key functions of the forest are: 1) ecological, since they ensure the absorption of carbon dioxide, participate in the regulation of the water balance, as well as the preservation of biodiversity; 2) provide the cycle of substances necessary for the existence of humanity; 3) perform a cultural function. Therefore, forests are not just a resource, but a living ecosystem that ensures the ecological balance of the planet. It is proven that forestry is a socially important and necessary sphere of activity, which includes a systematic set of scientifically substantiated legal, organizational, managerial, environmental, financial and material and technical actions and measures aimed at implementing following functions: a) ecological, - climate regulation, soil protection, biodiversity preservation); b) economic, - obtaining wood, non-timber products; social, - recreation, cultural value, supporting the vital activities of communities, etc. And therefore, it represents not just the cultivation and harvesting of forests, but also a comprehensive system of forest management as living natural resources, which are of strategic importance for ecological stability, social and economic well-being of society. It has been established that in Ukraine, as in many countries of the world, forests are under threat due to illegal logging, climate change, fires, the spread of pests, etc. This, in turn, requires the formation and implementation of an effective state policy in the field of forest use, which would combine economic feasibility, environmental sustainability and legal responsibility. Achieving the goals of the relevant policy is considered possible by implementing balanced and effective state supervision and control over forestry management.